Geotechnical slope analysis - Chowdhury, Robin; Flentje, Phil; Bhattacharya, Gautam (CRC Press, 2010)
This reference book gives a complete overview of the developments in slope engineering in the last 30 years. Its multi-disciplinary, critical approach and the chapters devoted to seismic effects and probabilistic approaches and reliability analyses, reflect the distinctive style of the original. Subjects discussed are: the understanding of slope performance, mechanisms of instability, requirements for modeling and analysis.